PENENTUAN AKTIVITAS ENZIM MANANASE DARI BERBAGAI MIKROORGANISME DI INDONESIA DAN PERANANNYA DALAM BIDANG PANGAN: KAJIAN PUSTAKA - Hermawan Seftiono (AGROINTEK, 2017)
Mananase is an enzyme that is involved in producing prebiotic, namely manooligosaccharide.In Indonesia, research about mananase enzyme has started by using several types ofmicroogranisms. Based on available reports, it seems that data collection is needed in order todetermine the most optimal mananase enzyme producer. From among 20 microorganisms, itshowed that Isolat SM – 14 (Bacillus sp.) has 119.44 U / ml activity with 19.55 U / mg specificactivity in locus bean gum substrate. The highest enzyme activity is the most potential whenapplied as manooligosaccharide producer in food industry. Manooligosaccharide can beapplied to various products such as cookies, chocolate, candy, and soft drinks.